PERAN DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI JAWA TIMUR DALAM MENANGANI HOAKS - Roro Trinil Widyaningrum; Suprihatin (LPPM Stikosa-AWS, 2025)
This research aims to analyze the role of the Communication and Informatics Office (Diskominfo) of East Java Province in addressing hoaxes circulating within society. The phenomenon of hoaxes has become increasingly prevalent in the digital era, potentially causing public unrest and undermining trust in the government. Therefore, effective public communication strategies and comprehensive digital literacy programs are required to mitigate the spread of false information. This study employs a qualitative descriptive method, with data collected through in-depth interviews, document studies, and observation of activities conducted by Diskominfo East Java. Data were analyzed using reduction, presentation, and conclusion drawing techniques to provide a comprehensive understanding of the implemented strategies. The findings indicate that Diskominfo East Java plays two main roles: preventive and curative. The preventive role is carried out through digital literacy programs, public awareness campaigns, and educational initiatives via social media to encourage critical thinking in evaluating information. The curative role is implemented through clarifications of false news via the website klinikhoaks.jatimprov.go.id, collaborations with mass media, and reports from the public. The public communication strategies applied combine informational, persuasive, and participatory models, thereby building public trust and reducing the spread of hoaxes. This research concludes that Diskominfo East Java’s role in handling hoaxes is crucial in maintaining social stability, enhancing digital literacy among citizens, and strengthening government public communication. The study recommends strengthening cross-sector collaboration, enhancing human resource capacity, and optimizing digital technology utilization in hoax management strategies.